Manajemen Pelayanan Berbasis Spiritualitas Islam: Pendekatan Tafsir Maudhu’i terhadap Prinsip-Prinsip TQM - Dermawan, Herman; Somantri, Ace; Salam, Mochamad Fadlani (FASTABIQ: JURNAL STUDI ISLAM, 2025)
This article examines the urgency of improving service quality within Islamic educational institutions, particularly in response to the growing disparity between rising public expectations and suboptimal service practices. Grounded in the principles of Total Quality Management (TQM), this study aims to integrate service management concepts with Islamic spiritual values derived from the Qur’an and Hadith. Employing a descriptive qualitative approach and thematic exegesis (tafsir maudhu‘i), the article analyzes Qur'anic verses relevant to service ethics and practice.From the provider’s perspective, Surah Al-Hashr [59]: 9 emphasizes sincerity, altruism, and the willingness to prioritize others' needs, as exemplified by the Ansar. From the customer's standpoint, Surah An-Nisa’ [4]: 29 highlights the principle of mutual consent in transactions, while Surah An-Nisa’ [4]: 58 underscores the importance of trustworthiness and justice in equitable service delivery. The Prophetic traditions further reinforce the view of service as a form of worship that promotes ease, assistance, inner peace, and spiritual elevation.The study concludes that integrating Islamic values into service management enhances not only procedural quality but also enriches the moral and ethical dimensions of service. This integration is particularly relevant in advancing both academic and managerial excellence in Islamic educational institutions. Keywords: Service management; Islamic values; Thematic exegesis; Total Quality Management; Service ethics